UPAYA MASYARAKAT WAKATOBI DALAM MENJADIKAN TAMAN NASIONAL WAKATOBI SEBAGAI CAGAR BIOSFER DUNIA TAHUN 2012 - Ervina Diyati; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research describes the efforts of Wakatobi society in making Wakatobi National Park as the world's biosphere reservation by UNESCO. Since long time ago, indigenous people of Wakatobi had done the environmental conservation through the folklore. Through the folklore Wakatobi people are able to build awareness in the society about the importance of environmental conservation of Wakatobi itself.This research uses international tourism theory and pluralism perspective. In the international relations, plurarism is not only about the relation between states, but also relationships between individuals and interest groups where the state does not always play the main actor and single actor. The data are collected through books, journals and internet media. The level of analysis used is the group analysis level. This analysis level assumes that the policy adopted by a decision maker is influenced by the groups around it.In July 2012 the United Nations Educational and Cultural Organization (UNESCO) officially decided Wakatobi National Park as the World's Biosphere Reservation because of the three interests of local Wakatobi society, such as wisdom, environmental sustainability and sustanaible economic interests of the society. The three interests that encourage the UNESCO make the marine area of Wakatobi National Park as the center of the World's Biosphere Reservation.Keywords : Wakatobi, UNESCO, National Park, Environment